THE ROLE OF THE SHARIA SUPERVISORY BOARD (SSB) IN MODERATING THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE OF ISLAMIC BANKS IN INDONESIA - Siswanti, Indra; Risman, Asep; Elmi, Farida; *, Markonah; Cahaya, Ferry (The International Journal of Accounting and Business Society, 2021)
Purpose — The aims of this research to examine and analyze the extent of the role of the sharia supervisory board (SSB) in moderating the effect of good corporate governance on the financial performance of Islamic banks in Indonesia.  Design/methodology/approach — Population in this research is 14 (fourteen) Islamic banks in Indonesia and the sample used in this research is 9 (nine) Islamic banks that have published financial reports, good corporate governance reports, and annual reports for the period 2010 - 2019. This research data processed were processed using reviews-10.Findings — The results of this research stated that good corporate governance has a significant effect on the financial performance of Islamic banks. The sharia supervisory board (SSB) moderates the effect of good corporate governance on the financial performance of Islamic banks in Indonesia.Practical Implications — The chow test stated chosen model as fixed effects, then the Housman test stated chosen model as random effects. Thus the model used in this research is a random effect.Originality/value — To complete the results, this research used in-depth interviews with practitioners of Islamic banks in Indonesia, specifically the departement of compliance with Islamic banks.Keywords Good corporate governance, Sharia  Supervisory Board, financial  performancePaper Type Research Paper.